ADH evolution and the phylogenetic footprint. - Dorit, R.L.; Ayala, F.J. (Journal of Molecular Evolution, 1995)
The evolution of any given protein reflects the interplay between proximal selective forces involving the conservation of protein structure and function and more general populational factors that shape the action and efficiency of natural selection. In an attempt to address that interplay, we have analyzed patterns of amino acid replacement within a well-conserved molecule, alcohol dehydrogenase (ADH), in the Drosophilidae. A sliding window, moved along the protein sequence in order to quantify the extent of change at each amino acid position, reveals heterogeneous amounts of replacement across the molecule when all ADH sequences are analyzed simultaneously. Surprisingly, the replacement profile for ADH differs significantly in the melanogaster, mulleri, and Hawaiian subgroups, reflecting the imprint of the differing evolutionary histories of each of these assemblages on the evolution of this conservative molecule.